Reinforcement Strain and Potential Failure Surface of Geogrid Reinforced Soil-Retaining Wall under Horizontal Seismic Loading - Sihan Li; Xiaoguang Cai; Liping Jing; Honglu Xu; Xin Huang; Chen Zhu (Shock and Vibration)
This paper presents experimental results from shaking table tests on two reduced-scale geogrid reinforced soil-retaining walls (RSRWs) constructed using standard soil, modular facing blocks, and uniaxial geogrid reinforcement to investigate the distribution of the geogrid strain and the mode of potential failure surface for dynamic loading conditions. Similitude relationships for shaking table tests in a 1 g gravitational field were used to scale the specimen geometry, applied characteristics of the earthquake motions. The lateral displacement of the top model is sufficiently large for the top-model block to fall down, and the RSRW is thus destroyed. The tensile strain at the lower part is greater than that at the upper part of the RSRW. The tensile strain in different layers for two-tiered RSRW is consistent with single-step RSRW. On comparing the measured maximum tensile strain lines of the geogrid with the result of the existing calculation method of the potential failure surface, it can be observed that the existing partial calculation method is conservative. Based on the calculation methods of various potential failure surfaces and the measured data, the use of a two-tiered fold-line failure surface is proposed for the two-tiered RSRW while taking into consideration the width of the platform. And it is advised that the failure surface calculation method of BS8006 be used as the calculation method for the potential failure surface of the single-step RSRW under dynamic motion.